Construções com o verbo agarrar em Português Brasileiro e Europeu - Coelho, Carolina Medeiros (2013)
In this paper we describe and analyze qualitatively the constructions with the verb agarrar in oral and written texts of both Brazilian and European Portuguese of the twentieth century. The theoretical perspective used combines the assumptions of the Functional Linguistics and the Cognitive Linguistics, named Cognitive-Functional Linguistics, in which we assume the studies about Grammaticalization and the Constructions Grammar. The data analyzed were collected from Corpus do Português and the corpus organized by Silva (2005), in which we identified three types of constructions, the transitive, the paratactic and the subordinate. And the syntactic configuration they present are: [Vagarrar COMPL], [V1agarrar (e) V2fin] and [V1agarrar (a) V2nonfin], respectively. The transitive constructions are formed basically by a verb-noun sequence and they encode, prototypically, the physical and perceivable change on the location of the object. However, when the object presents a more abstract semantic value, the change of location is metaphorical, therefore, these constructions were divided into canonical and non-canonical, respectively. The paratactic are formed by two verbs, V1 and V2, both inflected, and that may or may not be connected by the conjunction e (and). Those constructions have a focusing function since the V1 serves as a marker of focus, highlighting the event described by V2. The subordinate, in turn, are also formed by two verbs. However, in subordinate construction, V1 is an auxiliary verb that carries all morphological information of time, mode, number and person while V2 is the main verb and it is used in its nonfinite form. This construction encodes the beginning of the action expressed in V2, and V1, stands as an inceptive auxiliary. We conclude that the occurrence of the verb agarrar in these three constructions is enabled through the metaphor of movement, the verb interacts with the constructions so that the movement is coded differently in each one. In transitive, the movement causes the change of location of the object; in paratactic, the movement is metaphorical and V1 leads the listener/reader s attention to the action expressed by V2; and in the subordinate, the movement, also metaphorical, encodes the beginning of the action expressed by the second verb.